The Israel/Palestine reader - Dowty, Alan 1940- (Polity, 2019)
From Mark Twain to Theodor Herzl, Gamal Abdul Nasser, Golda Meir, Anwar Sadat, Ezer Weizman, Ehud Barak, Marwan Barghouti, Mahmoud Abbas, Benjamin Netanyahu, John Kerry, and dozens of others, the first-hand narratives brought together in this Reader bring the conflict to life as seen by those closest to it